The Effect of African Leaf Extract (Vernonia amygdalina) on Blood Sugar Levels and Wound Healing in Mice with Type 2 Diabetes Mellitus - Sharfina, Mazaya; Kuswanti, Nur; Khaleyla, Firas (LenteraBio : Berkala Ilmiah Biologi, 2025)
Long-term uncontrolled hyperglycemia in diabetes mellitus can lead to chronic complications, one of which is diabetic ulcers. African leaves have metabolite compounds that act as antidiabetics and accelerate wound healing. This study aims to identify the best effect and dose of African leaf extract on blood sugar levels and wound healing in Type 2 DM (T2DM) mice. This study used 24 male DDY mice grouped into six groups, namely negative control (A), positive control (B), metformin (C), African leaf extract doses of 75 mg/kgBW (D), 100 mg/kgBW (E), and 125 mg/kgBW (F). The induction of T2DM was done orally with a high-fat diet (HFD) and alloxan intraperitoneally. Wounds were made on the dorsal part of the mice as long as 1 cm. Administration of the extract was done orally. Wound healings were measured macroscopically based on the rates of wound healing and microscopically based on the density of the collagen fibers and the number of fibroblast cells. The data on fasting blood sugar levels, wound healing rates, and ulcer histology were analyzed statistically. The results showed that African leaf extract had a significant effect (p<0.05) on fasting blood sugar levels and wound healing, both macroscopically and microscopically. The 125 mg/kgBW dose of African leaf extract had the best result for blood sugar and wound healing. Thus, the African leaf extract is potentially useful for diabetic drugs and diabetic wound/ulcer healing.